Hipertexto nas práticas de ensino de língua portuguesa: uma análise de planos de aula do portal do professor do MEC - Pereira, Gabrielle Costa [UNIFESP] (2020)
This research, whose theme is hypertext in the teaching of Portuguese, aims to analyze how it is addressed in lesson plans available on the Ministry of Education's Teacher Portal. The search is justified because hypertext is a prominent topic in official documents such as the National Curriculum Parameters (PCNs) and the National Common Curricular Base (BNCC), and should be addressed in reading and writing practices in the classroom, in order to contemplate the varied languages that come into its composition. The study research is based on the fact that since then, in the era of digital culture, new challenges have been imposed on education, which makes it necessary to i) explore, with pedagogical objectives, the current technological resources and digital environments; ii) understand the forms of communication, interaction and performance in the world, as well as the cultural impacts that new technologies bring to society; iii) develop new ways of using and learning; iv) training to act in a society marked by constant technological advances. The corpus consists of four lesson plans extracted from the Teacher's Portal, which have hypertext as their object. In this work, hypertext is understood as a construct enhanced by traces of multiple connection between texts, non-linearity, non-delimitation, fluidity, variety of themes, textual genres and languages, resulting from the work carried out collaboratively by users interacting on the networks. In the wake of the discussion on hypertext, the concept of multi-tools is approached, which is closely related to multimodal or multisemiotic texts. In a scenario like the current one, in which the school is no longer the only source of knowledge and information, the practices of writing, reading, interaction and negotiation of meanings of the multiple languages present in the hypertext deserve to be highlighted.